Effects of rolling processing on the microstructures, mechanical properties and strain softening behavior of biodegradable Zn-0.06 Mg alloy - Chengwei Ji; Aibin Ma; Jinghua Jiang; Liwen Zhao; Xuefei Fang; Huan Liu; Dan Song (Journal of Materials Research and Technology, 2024)
Micro-alloyed Zn–Mg alloys have attracted extensive attention in the field of medical implant due to their excellent biosafety and moderate degradation rate. The low Mg content could compromise the improvement of strength, therefore, the appropriate rolling process was investigated to enchance strength and inhibit strain softening behavior of Zn-0.06 Mg alloy. The observed changes in microstructures, mechanical properties, and strain softening behavior of the as-cast alloy after three different rolling processing were consistent with those exhibited by the solid-solution alloy. The cold rolled alloys showed excellent strength due to their small average grain size and high initial dislocation density, however, they also exhibited noticeable strain softening behavior. Hot rolling processing can result in coarsening of the grains, reduction in dislocation density and introducing a large number of twins, which inhibited strain softening behavior but also leaded to a decrease in the strength compared with cold rolling. The hot-cold rolling processing can induce the formation of heterostructure, wherein coarse grains encircled fine grains, while high density dislocation regions and low density dislocation regions were uniformly distributed, which effectively inhibited strain softening behavior on the basis of maintaining good mechanical properties.